Analisis Pemasangan Kapasitor Bank sebagai Solusi untuk Mengurangi Drop Tegangan pada Penyulang Lowayu - Ari Purnomo Aji; Denny Irawan; Rini Puji Astutik (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
PLN as an electricity provider that serves all regions in Indonesia certainly always wants to provide the best service to its consumers, including PT. PLN Persero UP3 Gresik. Along with the increase in consumers, the company continues to develop distribution lines, however, because the addition of more and more lines makes the distribution cables longer and the load becomes greater, resulting in voltage drops and power factors decreasing in several feeders, including in the feeder network. LOWAYU, causing poor power quality.This research aims to find and obtain the magnitude of the power flow which includes active power, reactive power, apparent power and the magnitude of the power losses (losses) contained in the LOWAYU feeder network, the magnitude of the voltage and voltage drop on each bus on the network. LOWAYU feeder using the backward-forward method. And determine the value of reactive power required for the capacitor on each bus that experiences a voltage drop. Then a comparison will be made between the results of manual calculations using the backward-forward method and the results of simulation data using ETAP Power Station 19.0.1 software.From this research, it can be seen that the safe limit for the voltage drop value is still below 5% or above 5%, so it is necessary to add capacitor banks to improve the power factor and reduce the voltage drop value on distribution network buses that experience voltage drops.